Pacing: A Concept Analysis of a Chronic Pain Intervention - Kathryn Jamieson-Lega; Robyn Berry; Cary A Brown (Pain Research and Management)
BACKGROUND: The intervention of pacing is regularly recommended for chronic pain patients. However, pacing is poorly defined and appears to be interpreted in varying, potentially contradictory manners within the field of chronic pain. This conceptual lack of clarity has implications for effective service delivery and for researchers’ ability to conduct rigorous study. An examination of the background literature demonstrates that while pacing is often one part of a multidisciplinary pain management program, outcome research is hindered by a lack of a clear and shared definition of this currently ill-defined construct.